The research development of STAT3 in hepatic ischemia-reperfusion injury - Yang, Hanwen; Zhang, Pengpeng; Wang, Qiang; Cheng, Ke; Zhao, Yujun (Frontiers in Immunology, 2023)
Ischemia-reperfusion injury (IRI) is a common complication of surgery, which can cause rapid deterioration of the liver function, increase the risk of graft rejection, and seriously affect the prognosis of patients. The signal transducer and activator of transcription 3 (STAT3) protein has been implicated in pathogenesis of IRI. STAT3 influences the mitochondria through multiple pathways and is also involved in apoptosis and other forms of programmed cell death. STAT3 is associated with Janus kinase (JAK), phosphoinositide-3 kinase (PI3K), and heme oxygenase-1 (HO-1) in liver IRI. The STAT3 pathway plays a dual role in IRI as it can also regulate lipid metabolism which may have potential for treating IRI fatty liver. In this review, we summarize research on the function of STAT3 in liver IRI to provide references for its application in the clinic.